2015
DOI: 10.3758/s13423-015-0923-3
|View full text |Cite
|
Sign up to set email alerts
|

Is mental effort exertion contagious?

Abstract: The presence of another person can influence task performance. What is, however, still unclear is whether performance also depends on what this other person is doing. In two experiments, two participants (A and B) jointly performed a Simon task, and we selectively manipulated the difficulty of the task for participant A only. This was achieved by presenting A with 90% congruent trials (creating an easy task requiring low effort investment) or 10% congruent trials (creating a difficult task requiring high effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Hence, the unconstrained actor’s modulation of movement height in response to the coactor’s obstacle may be interpreted as an expression of the co-represented cognitive effort. However, whereas Desender et al (2016) used an interference task where response times reflect cognitive effort, our dependent variable of movement height provides a measure of movement effort that is not necessarily related to cognitive effort.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the unconstrained actor’s modulation of movement height in response to the coactor’s obstacle may be interpreted as an expression of the co-represented cognitive effort. However, whereas Desender et al (2016) used an interference task where response times reflect cognitive effort, our dependent variable of movement height provides a measure of movement effort that is not necessarily related to cognitive effort.…”
Section: Discussionmentioning
confidence: 99%
“…First, it would be vital to check whether performing the same task simultaneously with another person leads to similar outcomes, i.e. better cognitive abilities (Desender et al, 2016, Eskenazi et al, 2013Shteynberg, 2010) or stronger sensory sensations (Boothby et al, 2014), and whether those results are different depending on the familiarity levels of co-experiencers. Second, only after consistently obtaining such results, we could start assessing whether the shared attention theory can actually explain those findings.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that participants exerted more effort when their partners were performing a hard task, compared to when their partners were performing an easy task. This finding suggested that the cognitive efforts exerted by someone performing a task could influence the cognitive efforts of others present in the same physical space and performing similar tasks (Desender et al, 2016). Further studies have shown that across a variety of tasks studied, when participants performed a task at the same time as others, their performance was superior compared to when they performed the same task alone.…”
Section: Amplification Of Intensity Of Experienced Emotions Due To Shmentioning
confidence: 96%
See 2 more Smart Citations